The Role of Intellectual Capital in Mediating the Impact of Knowledge Management and Innovation in the Halal Batik Industry of Yogyakarta - Susanto, Heri; Mubarok, Alvian Alvin; Oetomo, Hadi; Kurniawan, Dedi (Global Review of Islamic Economics and Business, 2024)
This study aims to investigate the role of intellectual capital in mediating the impact of knowledge management and motivation on halal small and medium-sized enterprises (SMEs) in the batik industry in Yogyakarta. Research on the mediating role of intellectual capital is still relatively novel in Indonesia. The study of the batik industry is particularly compelling, given that batik is an intangible asset recognized as UNESCO's cultural heritage. However, there is a noticeable decline in export value year by year. By focusing on halal batik SMEs, this study explores how halal certification can enhance these businesses' market appeal and export potential. The initial step of this research involves collecting data related to the research variables by distributing questionnaires to batik entrepreneurs in Yogyakarta. Subsequently, tests are conducted using PLS to analyze the results, examining the role of intellectual capital in mediating the impact of knowledge management and motivation on halal SMEs in the batik industry in Yogyakarta. The findings provide insights into how intellectual capital can influence the sustainability and growth of batik enterprises, offering strategies to counteract the declining export values and enhance the overall performance of these culturally significant businesses. Originality/Value: Unlike prior research, which focuses on global views and big industry, this study provides valuable insights for halal SMEs, particularly in the batik industry. The findings aim to elucidate how intellectual capital impacts the sustainability and growth of halal batik enterprises. It seeks to offer strategies to mitigate declining export values and enhance the overall performance of these culturally significant businesses, with a particular emphasis on leveraging the opportunities presented by halal certification.